Comparison of some important dairy traits of crossbred cows at Baghabarighat milk shed area of Bangladesh - Hossen, MS; Hossain, SS; Bhuiyan, AKFH; Hoque, MA; Talukder, MAS (Bangladesh Journal of Animal Science, 2012)
Data on 3637 cows of seven genetic groups at Baghabarighat milk shed area during the period from 1991 to 2000 were analyzed. The genetic groups were Pabna Milking Cows (PMC), ½Sahiwal×½PMC (SL×PMC), ½Frisian×½PMC (FN×PMC), ½Australian Friesian Sahiwal×½PMC (AFS×PMC), ½Sahiwal×¼Friesian×¼PMC [SL(FN×PMC)], ½Friesian×¼Sahiwal×¼PMC [FN(SL×PMC)] and ½Friesian×¼Jersey×¼PMC [FN(JR×PMC)]. The purpose of this study was to compare the productive (birth weight, lactation length, lactation yield, fat% and SNF%) and reproductive (age at first service, service per conception, postpartum heat period and calving interval) traits of different crossbred cows. The highest birth weight of calves was obtained as 29.78 kg in AFS×PMC, lactation yield as 2225.52 liters in FN(JR×PMC), fat% as 4.48 in SL×PMC and SNF% as 8.10 in FN(SL×JR). The longest lactation length was observed as 305.18 days in AFS×PMC. The shortest age at first service was observed as 26.83 months in FN(PMC×SL), postpartum heat period as 133.23 days in PMC and calving interval as 414.90 days in PMC. The lowest service per conception was found to be 1.22 in PMC cows. The high genetic variability of birth weight, lactation yield, fat and SNF% indicated that there are good opportunities for genetic improvement of these traits through selection. From the results, it is evident that the level of production of different crossbred cows found to be higher but important reproductive traits were significantly better on PMC. Thus it may be concluded that for long term sustainable development and conservation program for PMC should be initiated alongside with that of crossbred in this particular study area. http://dx.doi.org/10.3329/bjas.v41i1.11970